The relationship between vitamin D status and gestational diabetes mellitus: a case-control study - Somayeh Fallahnezhad; Aram Bahari; Bagher Pahlavanzade; Samaneh Hashemi; Davood Mosavat (Mashhad University of Medical Sciences, 2024)
Introduction: Gestational diabetes (GDM) is one of the most important causes of complications during pregnancy and has a high prevalence, so it is essential to identify the factors affecting its physiopathology as a way to prevent and treat it. Therefore, the present study was performed with aim to investigate the serum level of vitamin D in healthy and diabetic pregnant women. Methods: This case-control study was conducted in 2022-2023 on 198 pregnant women (99 with gestational diabetes and 99 without gestational diabetes in the control group) referred to the treatment centers of Abadan University of Medical Sciences. After obtaining consent from the subjects and recording demographic information, serum vitamin D levels were also recorded. Data were analyzed by SPSS software (version 24) and Independent T and Pearson correlation tests. P<0.05 was considered statistically significant. Results: The mean serum level of vitamin D in women with GDM was significantly lower than pregnant women in the control group (16.97 vs. 26.76 ng/ml). By grouping pregnant women based on age, gestational age, gravid and BMI, women with GDM had lower mean vitamin D levels than pregnant women in the control group (P<0.05). In the correlation analysis of women with GDM, vitamin D level had an inverse and significant relationship with 1-hour sugar (r=-0.212 and P=0.035) and 2-hour sugar (r=-0.223 and P=0.026), but no significant relationship with FBS level was observed. The sensitivity and specificity of vitamin D in the diagnosis of GDM at the cut-off point of 18.05 were 69.7% and 74.7%, and the positive and negative predictive value were 73.4% and 71.2%, and the overall accuracy was 72.2% and the level of agreement was moderate. Conclusion: Women with GDM had significantly less vitamin D, which can be considered a risk factor for GDM during pregnancy.